Biogas as an alternative energy source - Podeszwa, Ewelina; Biernat, Krzysztof (Studia Ecologiae et Bioethicae, 2014)
The advantages of biogas, apart from being just an alternative energy source, are its various possibilities of conversion. Chemical energy can be converted into biogas for heat, electricity and chemical energy of other compounds. Therefore, there are numerous opportunities for using energy from biogas. Some of them are used in stationary installations. Another application is as a fuel for vehicle engines by burning biomethane.